2018
DOI: 10.1103/physreve.98.043110
|View full text |Cite
|
Sign up to set email alerts
|

Slip-flow lattice-Boltzmann simulations in ducts and porous media: A full rehabilitation of spurious velocities

Abstract: Slip flow in ducts and porous media is simulated using lattice-Boltzmann method incorporated with interfacial force models. The dependence of the results on the viscosity, LBM scheme (D3Q15 and D3Q19) and the relaxation time model (single or multi-relaxation time) is investigated. The severity of spurious velocities (arisen from classic and advanced interfacial force models) is discussed that leads to entirely non-physical results for whole flow rates (0.027 < Re < 10.7). A simple method based on superposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 83 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…Then, by tuning magnitudes G w and G b , we increase or decrease the density profile approaching the wall surface to match the different wettability values (see supporting information Text S6). We use the superposition of two conditions of solution to exclude the nonphysical velocities and rehabilitate the simulations (Aminpour et al, ). Researchers have tested against the above proposed frame with density distribution, velocity distribution, and flow enhancement in a total of 22 published cases of water flow through nanotubes made of different materials and dimensions, as shown in Figure .…”
Section: Multiscale Water Flow Simulation Methodsmentioning
confidence: 99%
“…Then, by tuning magnitudes G w and G b , we increase or decrease the density profile approaching the wall surface to match the different wettability values (see supporting information Text S6). We use the superposition of two conditions of solution to exclude the nonphysical velocities and rehabilitate the simulations (Aminpour et al, ). Researchers have tested against the above proposed frame with density distribution, velocity distribution, and flow enhancement in a total of 22 published cases of water flow through nanotubes made of different materials and dimensions, as shown in Figure .…”
Section: Multiscale Water Flow Simulation Methodsmentioning
confidence: 99%
“…In this study using a continuum approach incorporated with the interface interaction models, we study the flow of Newtonian fluids between flat walls, in tubes and porous media when the wettability effects are considerable. The method is validated for flow simulations in effects of interfacial interactions in previous studies [2,[234][235][236][237][238] and also here ( Fig. 6.1).…”
Section: Introductionmentioning
confidence: 63%
“…Secondary laminar flow induced by the curvature of the pipes and enhanced by pulsating flow has been also frequently studied due to its applications, particularly in mixing and heat transfer processes [147][148][149][150]. In the presence of porous media, it is also shown that the pore-scale features may play a critical role in micro-scale flow behaviour, also governing the macroscopic transport regimes [1,188,297]. In nature, oscillations of aquifer flow have been found to greatly influence transport mechanisms and mixing enhancement [151], and the saline groundwater 92 CHAPTER 7.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations